(untitled) (Altre Modernità, 2012)
In this essay we apply Edward Said’s theory of Orientalism to a study of Lebanese culture and identity. The starting point is pedagogical, the intellectual license assumed by western thinkers in constructing, interpreting and articulating the history of the East. However, does this theory help us to understand the crisis of identity that has been the source of so much conflict in Lebanon in the past? What we contend is that though undeniably Said’s Orientalism has generated arguments and counterarguments, it remains, as regards the history of Lebanon, a reductive concept that simplifies the difference between European outsider and Eastern “other”. Rather, it is necessary to take into account what in contemporary sociological terms is a far more complex encounter between Christians, Muslims and Jews. Geographically, the physical landscape encompasses division and even inaccessibility. This cultural palimpsest resists homogeneity: Maronites, for example, the most prominent Christian sect, have since the twelfth century looked to Rome for spiritual guidance; Sunnis and Shiites assert their own denominational allegiances; and Jews, though their presence has been almost completely eliminated, their identity remains evident in the electoral registers, and emblematised in the empty places of worship. Our modus operandi is to adopt an ontological and epistemological approach in the study of Orientalism, while, at the same time, exploring the realities of sectarian divisions in Lebanon, which determine how people, in the formation of identity, respond to and interact with their immediate surroundings. Bearing in mind the inherent religious differences that divide the Lebanese, where then is otherness to be located? Arguably, the ideological fissures that exist between them have allowed outsiders to penetrate their culture and to monopolise their knowledge.